One-Bath Pretreatment for Enhanced Color Yield of Ink-Jet Prints Using Reactive Inks - Wei Ma; Kezhan Shen; Shuang Li; Meichen Zhan; Shufen Zhang (Molecules, 2017)
In order to facilely increase the color yield of ink-jet prints using reactive inks, one-bath pretreatment of cotton fabrics with pretreatment formulation containing sodium alginate, glycidyltrimethylammonium chloride (GTA), sodium hydroxide, and urea is designed for realizing sizing and cationization at the same time. The pretreatment conditions, including the concentrations of GTA and alkali, baking temperature, and time are optimized based on the result of thecolor yield on cationic cotton for magenta ink. The mechanism for color yield enhancement on GTA-modified fabrics is discussed and the stability of GTA in the print paste is investigated. Scanning electron microscopey, tear strength, and thermogravimetric analysis of the modified and unmodified cotton are studied and compared. Using the optimal pretreatment conditions, color yield on the cationic cotton for magenta, cyan, yellow, and black reactive inks are increased by 128.7%, 142.5%, 71.0%, and 38.1%, respectively, compared with the corresponding color yield on the uncationized cotton. Much less wastewater is produced using this one-bath pretreatment method. Colorfastness of the reactive dyes on the modified and unmodified cotton is compared and boundary clarity between different colors is evaluated by ink-jet printing of colorful patterns.